2012
DOI: 10.1002/ange.201201042
|View full text |Cite
|
Sign up to set email alerts
|

Selektiver Nachweis von Ethylengas mit Kohlenstoffnanoröhren als Hilfsmittel in der Fruchtreifebestimmung

Abstract: Ethylen als kleinstes Pflanzenhormon ist an vielen Entwicklungsprozessen beteiligt. Als Beispiele sind die Fruchtreifung zu nennen, die durch Ethylen initiiert wird, der Saataufgang und die Blüte sowie das Verwelken von Blättern und Blumen. [1] Der geschwindigkeitsbestimmende Schritt im Biosyntheseweg von Ethylen, der von Yang et al. untersucht wurde, wird durch die 1-Aminocyclopropan-1-carbonsäure-(ACC)-Synthase katalysiert. [2] In mehreren Entwicklungsphasen einer Pflanze wird Ethylen produziert, und auch ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Random networks of functionalized SWCNTs have produced sensors that are inexpensive to fabricate, operate at room temperature, and have ultra-low power requirements. [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
mentioning
confidence: 99%
“…In einer jüngsten Veröffentlichung beschrieben nun Swager und Mitarbeiter6 die Entwicklung eines neuartigen Ethylensensors basierend auf der nichtkovalenten Funktionalisierung eines SWNT‐Netzwerks mit einem Kupfer(I)‐Komplex (Abbildung 1 a). Ethylen ist das kleinste Pflanzenhormon.…”
unclassified
“…Bei Einwirkung von Ethylengas bindet 1 ein Ethylenmolekül und bildet den Cu‐Ethylen‐Komplex 2 , was zu einer Änderung des elektrischen Widerstandes des SWNT‐Netzwerks führt. b) Relatives elektrisches Ansprechverhalten von 1 ‐SWNT‐Sensoren gegenüber Ethylengas, das von verschiedenen Früchten (je 100 g) emittiert wurde 6…”
unclassified
“…In an article in Angewandte Chemie , Timothy Swager and co‐workers6 describe the clever design of a novel ethylene sensor, which included the noncovalent functionalization of SWNT network with a copper(I) complex (Figure 1 a). Ethylene is the smallest plant hormone that initiates the ripening of fruit and influences other growth processes,7a and it is also a typical example of an analyte with low chemical activity and molecular polarity.…”
mentioning
confidence: 99%